Adjuvant treatment with yupingfeng granules for recurrent respiratory tract infections in children: A systematic review and meta-analysis - Zhang, Lu; Wang, Xuqiong; Wang, Dong; Guo, Yinling; Zhou, Xinying; Yu, Haiyan (Frontiers in Pediatrics, 2022)
Abstract Background: Yupingfeng Granules (YPFG) is helpful in a variety of chronic respiratory infections. Several clinical studies have evaluated its effectiveness and safety in treating children with recurrent respiratory tract infections (RRTIs); However, evidence for the use of YPFG has yet to be conclusively confirmed. Objective: This study aimed to demonstrate the efficacy and safety of YPFG in treating children with RRTIs. Methods: By searching PubMed, Embase, Web of Science, Cochrane Library, Clinical Trials, Chinese Clinical Trial Registry, SinoMad, China National Knowledge Infrastructure (CNKI), Wanfang Database, and Chinese Scientific Journals Database (VIP) up to April 1, 2022, randomized controlled trial (RCTs) of adjuvant YPFG therapy for RRTIs in children. Literature that met the criteria was screened, literature quality assessed, and data extracted for systematic review and meta-analysis. Results: A total of 15 RCTs were included. Data analysis showed that the overall clinically effective rate of the YPFG group was significantly higher than that of the control group [risk ratio (RR)= 1.21, 95% CI (1.13, 1.29), I2=57%, P<0.00001]. Compared to the control group, three serum immunoglobulin levels were significantly increased in the YPFG group: IgA level [weighted mean difference (WMD)=0.40, 95%CI (0.20,0.61), I2=98%, P=0.0001]; IgM level [WMD=0.37, 95%CI (0.14,0.60), I2=97%, P=0.002]; IgG level [WMD=2.89, 95%CI (1.61,4.17), I2=99%, P<0.0001]. The TNF- level in the YPFG group was significantly lower [standardized mean difference (SMD)= -1.47, 95%CI (-2.26, -0.68), I2=91%, P=0.0003). Conclusions: Adjuvant YPFG therapy appears to improve clinical efficacy and immunity in children with RRTIs. However, the effectiveness and safety of YPFG still need further verification. Keywords: Yupingfeng granules, recurrent respiratory tract infections, children, systematic review, meta-analysis Systematic Review Registration: [https://inplasy.com/inplasy-2022-3-0150/], identifier [INPLASY202230150].